Sagittal and vertical craniofacial growth and attainment of circumpubertal middle phalanx maturation (MPM) stages: A multiple regression study - Perinetti, Giuseppe; Sverko, Davide; Dal Borgo, Beatrice; Contardo, Luca (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Introduction: Orthodontic treatment for most of the skeletal malocclusions have specific optimal timing according to the skeletalmaturation phases. The knowledge of whether attainment of a specific maturation phase is associated with the different sagittal andvertical craniofacial growth pattern then becomes of clinical relevance.Aim: This cross-sectional study evaluated whether sagittal and vertical craniofacial growth pattern, has an association with the age ofattainment of the circumpubertal skeletal maturation phases.Materials and methods: A total of 300 subjects (170 females and 130 males) were included in the study (mean age, 12.0 ±1.5 years; range, 8.3-15.6 years). These subjects were equally distributed in the circumpubertal middle phalanx maturation (MPM) stages 2, 3 and 4. Subsequently,multiple regression models were run for each MPM stage group to assess the significance of the association of cephalometric parameters(SNA, SNB, ANB, PP/MP, CoGoMe, SN/MP and NSBa angles) with age of attainment of the corresponding MPM stage (in months).Results: Only sex yielded significant associations, with females having anticipated attainment of each of the circumpubertal MPM stage.Conclusion: These results show no significant correlations of the different sagittal and vertical cephalometric parameters with the ageof attainment of the circumpubertal skeletal maturation phases.